Do Narcissists Enjoy Visiting Social Networking Sites? It Depends on How Adaptive They Are - Shi, Yuanyuan; Luo, Yu L. L.; Yang, Ziyan; Liu, Yunzhi; Bao, Hanwushuang (Frontiers in Psychology, 2018)
Previous evidence suggests that narcissistic people tend to visit social networking sites (SNS) frequently, but the emotions accompanying their engagement on such sites has not been a significant subject of study. Therefore, we examined the relationship between narcissism and the affective experience on SNS in two different samples. To do so, we not only examined narcissism as a whole but also distinguished between adaptive and maladaptive narcissism. Results of the two studies consistently showed that: 1) narcissism as a whole was not correlated with the SNS affective experience; 2) maladaptive narcissism was predictive of a worse affective experience on SNS; and 3) partly due to a positive correlation with self-esteem, adaptive narcissism was associated with a better SNS affective experience. In addition, these findings held with SNS activities considered in simultaneity. The present research extends our understanding of the relationship between narcissism and social networking as well as that between emotion and social networking.